THE VALUE OF MISOPROSTOL IN PATIENTS USING NSAIDs - Levent DEMİRTÜRK and Saadeddin HÜLAGÜ and İlhan KARABEKİR and Sabahattin GÜL and Zeki ÇANKIR and Mehmet ALTIN and Metin ERTÜRK (Turkish Journal of Gastroenterology, 2020)
-